Mutational and phenotypic spectrum of phenylalanine hydroxylase deficiency in Zhejiang Province, China. Issue 1 (December 2018) - Chen, Ting; Xu, Weize; Wu, Dingwen; Han, Jiamin; Zhu, Ling; Tong, Fan; Yang, Rulai; Zhao, Zhengyan; Jiang, Pingping; Shu, Qiang
Abstract Phenylalanine hydroxylase deficiency (PAHD), one of the genetic disorders resulting in hyperphenylalaninemia, has a complex phenotype with many variants and genotypes among different populations. Here, we describe the mutational and phenotypic spectrum of PAHD in a cohort of 420 patients from neonatal screening between 1999 and 2016. The observed phenotypes comprised 43.57% classic phenylketonuria, 33.10% mild PKU, and 23.33% mild hyperphenylalaninemia, with an overall PAHD incidence of 1 in 20, 445. Genetic testing was performed for 209 patients and 72 variants including seven novel variants were identified. These included two synonymous and five pathogenic nonsynonymous variants (p.S36*, p.T186I, p.L255W, p.F302V and p.R413H). The most common variant among all patients was p.R243Q, followed by p.R241C, p.Y204C, p.R111* and c.442-1G > A. Variants p.R53H and p.F392I occurred only in MHP with 19.3% and 8.0% of the observed alleles respectively. The genotypes p.[R241C];[R243Q], p.[R243Q];[R243Q], and p.[Y204C];[R243Q] were abundant across all PAHD patients. The distributions of the null allele and the three defined genotypes, null/null, null/missense, and missense/missense, were significantly different between the cPKU and mPKU patients. However, no significant differences were found between mPKU and MHP patients, indicating that other modifier factors influence the phenotypic outcome in these patients. The data presented here will provide a valuable tool for improved genetic counseling and management of future cases of PAHD in China.